The proxy war between Iran and Saudi Arabia: The case of the Yemeni Civil War - Settembrini, Maria Maddalena (2019)
The conventional understanding of the term Proxy War or War by Proxy was defined during the Cold War period as a confrontation between two great powers using substitute actors to avoid a direct confrontation (Bar-Siman-Tov 1984). Focusing on the Middle East region, it is widely acknowledged that Iran and Saudi Arabia are involved in a long-term animosity that causes a strategic imbalance in regional policies. The Iranian Revolution of 1979 catapulted these two States into bitter rivalry. The fall of Saddam Hussein, the establishment of a Shiite Iraq and the Arab Springs of 2011, have increased the tensions between Saudi Arabia and Iran. Both countries have not a direct military confront yet, but they have undoubtedly divided the region into two armed camps, based on political and religious ideologies, seeking regional allies and continuing the exploitation of the weakest countries in the region in a series of proxy wars, from the conflicts in Iraq to the war in Syria and the recent Yemeni conflict. This thesis will analyse the current Saudi-Iranian rivalry and how it affects the Civil War in Yemen. The relevance in analyzing this conflict derives from the situation of oblivion in which it finds itself in the international debate, which may already be considered the worst humanitarian crisis of the last decade.